The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1111/1477-8947.12191
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development in East Africa: impact evaluation of regional agricultural development projects in Burundi, Kenya, Rwanda, Tanzania, and Uganda

Abstract: Investments in agricultural technologies, capacity building and policy harmonization are needed to support sustainable development across Africa. Regional development projects can facilitate the adoption of agricultural technologies and innovations across nation‐state borders and generate benefits for shared prosperity. This paper uses panel data from 1,160 smallholder households including beneficiaries and non‐beneficiaries from five countries in East Africa ‐ Burundi, Kenya, Rwanda, Tanzania, and Uganda. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 80 publications
(115 reference statements)
0
10
0
1
Order By: Relevance
“…According to Wahome et al (2021), the most important factors affecting banana production are labour and performance of agronomic management practices which include the use of quality planting materials, appropriate use of fertilizers, mulch and manure. One of the main recommended technologies is the use of tissue culture bananas whose adoption is less than 7% in Kenya and significantly lower in Uganda and Burundi (Warinda, Nyariki, Wambua, Muasya, & Hanjra, 2020). A recent impact study for Kenya showed positive yield effects of tissue culture banana adoption but also pointed out the importance of good extension and proper plantation management (Murongo, Wangai, Mwine, & Ayuke, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wahome et al (2021), the most important factors affecting banana production are labour and performance of agronomic management practices which include the use of quality planting materials, appropriate use of fertilizers, mulch and manure. One of the main recommended technologies is the use of tissue culture bananas whose adoption is less than 7% in Kenya and significantly lower in Uganda and Burundi (Warinda, Nyariki, Wambua, Muasya, & Hanjra, 2020). A recent impact study for Kenya showed positive yield effects of tissue culture banana adoption but also pointed out the importance of good extension and proper plantation management (Murongo, Wangai, Mwine, & Ayuke, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from fertility management, other recommended practices including pest and disease control, weeding, irrigation, desuckering, deleafing and debudding (removal of the male bud) should also be given adequate emphasis to enable farmers to achieve stable yield levels (Warinda et al, 2020). However, according to Muthee et al (2019) very few banana farmers in Embu County have adopted these banana management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in Ethiopia, several empowerment indicator variables (including input in production decisions, autonomy in plot management, membership in farmers' groups and the ability to speak in public) positively influenced women's participation in different stages of agricultural research (Mulema et al, 2019). In Kenya, and Uganda, investments in agricultural technology and capacity-building contributed to gender equality and closing the gender gap in agriculture (Warinda et al, 2020).…”
Section: Successes Of and Barriers To Women's Empowermentmentioning
confidence: 99%
“…For instance, public organizations are employing structured cross-sectoral and multi-stakeholders' approaches for integrating governments, international players, donors, business players, third-sector and local communities in sustainable decision making (Goll, Uhl, & Zwiers, 2019). In East African region, governments are incorporating sustainable development strategies through stakeholder involvement with an aim of promoting long-term positive impacts of investment projects (Warinda, Nyariki, Wambua, Muasya & Hanjira 2020). In Kenya, participation of public and stakeholders in development projects is not only anchored in the Constitution of Kenya 2010 but also guided by public participation Act of 2019.…”
Section: Introductionmentioning
confidence: 99%